Getting started in stock investing & trading - Thomsett, Michael C. (Getting started in, 2013)
A new edition of the bestselling illustrated guide to stocks This popular and easy-to-use guide to understanding and investing in stocks combines basic and non-technical explanations with many other features: illustrations, definitions in context, examples, charts, key points, and valuable resources including online supplemental learning tools